Synthesis of 4-Organoselanyl-1H-pyrazoles: Oxone®-Mediated Electrophilic Cyclization of α,β-Alkynyl Hydrazones by Using Diorganyl Diselenides - Perin, Gelson; Nobre, Patrick C.; Mailahn, Daniela H.; Silva, Márcio S.; Barcellos, Thiago; Jacob, Raquel G.; Lenardão, Eder J.; Santi, Claudio; Roehrs, Juliano A. (Synthesis, 2019)
A simple and efficient method for the synthesis of 4‑organoselanyl-1H-pyrazoles has been developed, taking place under metal- and halogen-free conditions. Electrophilic species of selenium were easily generated in situ by the reaction of diorganyl diselenides with Oxone® in ethanol as solvent in an open-flask at 70 °C. These electrophilic selenium species were employed in the selenylation/cyclization of α,β-alkynyl hydrazones, giving the title compounds in moderate to excellent yields. The final species of selenium obtained from the reaction of diphenyl diselenide with Oxone® were characterized by 77Se NMR spectroscopy and high-resolution mass spectrometry (HRMS).
Keywords: selenium; Oxone®; 1H-pyrazoles; cyclizations; alkynes; hydrazones